2022
DOI: 10.1016/j.xagr.2021.100049
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of COVID-19 maternal and neonatal clinical features and pregnancy outcomes up to June 3, 2021

Abstract: Objectives COVID-19 is a rapidly changing and developing emergency that requires constant re-evaluation of available data. We report a systematic review and meta analysis based on all published high quality data up to and including June 3rd 2021 on the maternal and neonatal outcomes in pregnant women infected with the Coronavirus Disease 2019 (COVID-19). Data Sources PubMed, SCOPUS, MEDLINE, ClinicalTrials.gov, and Web of Science databases were queried from inception up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 22 publications
6
67
1
4
Order By: Relevance
“…It seems that the timing of delivery of patients with a positive SARS-CoV-2 test result can be rescheduled considering the severity of COVID-19 infection and obstetric indications such as gestational age and fetal well-being, maternal cardiac disease, diabetes, preeclampsia, and existing comorbidities. Clinical data including over 42,000 pregnant women indicated that the ratio of cesarean to VD was higher (53.2% CS vs. 41.5% VD) in those populations and that pregnant women who were exposed to a heavier course of COVID-19 were more likely to have a risk of preterm delivery [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the timing of delivery of patients with a positive SARS-CoV-2 test result can be rescheduled considering the severity of COVID-19 infection and obstetric indications such as gestational age and fetal well-being, maternal cardiac disease, diabetes, preeclampsia, and existing comorbidities. Clinical data including over 42,000 pregnant women indicated that the ratio of cesarean to VD was higher (53.2% CS vs. 41.5% VD) in those populations and that pregnant women who were exposed to a heavier course of COVID-19 were more likely to have a risk of preterm delivery [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current state of knowledge regarding SARS-CoV-2 infection in the first few days of life indicates that sharing the room of a COVID-19-affected mother and infant and taking precautions minimizes the risk of infection and provides more health and emotional benefits than potential harm [ 76 , 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women with comorbidities are considered at a greater risk of experiencing severe diseases, morbidity, and mortality (POGI, 2020). COVID-19 likely increases the risk of premature birth, preeclampsia, stillbirth, neonatal death, and maternal death (Marchand et al, 2022). It is more threatening that 1.30% of 11,758 pregnant women infected with COVID-19 died, and and 20% of the postpartum women, had comorbidities (Karimi et al, 2021).The Indonesian Ministry of Health has changed health guidelines for checking pregnancy, childbirth, and postpartum during the COVID-19 pandemic, for example, delay in pregnancy programs and routine pregnancy examinations for suspect and positive confirmed mothers, and change in mode of second-trimester pregnancy examination (Ministry of health Republic of Indonesia, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…It was though suggested in this multi-country cohort that no systematic pattern of differences in maternal outcomes were measured between participating countries (7). Therefore, the direct impact of COVID-19 on pregnant and recently pregnant women in Africa, and thus the true global impact, is still not well described (8).…”
Section: Introductionmentioning
confidence: 99%